Corneal curvature in young high myopic undergraduates in southern Nigeria - Okukpon, Juno Ohiremere; Ojo, Oluwashola Michael (International Journal of Research in Medical Sciences, 2018)
Background: Corneal curvature is important for contact lens fitting and management, ocular aberration analysis, corneal refractive surgery as well as diagnoses and management of corneal pathological conditions such as keratoconus and it is also an important biometric factor affecting refractive errors, myopia inclusive. Methods: This was an observational cross-sectional study conducted at the Optometry Teaching Clinic, Department of Optometry, University of Benin, Benin City, Edo State, Nigeria. Two hundred and twenty myopic eyes of 113 (54 males, 59 females) undergraduates students, between 16 and 25 years with myopia of -5.00 to -20.50 participated in this study. Non-cycloplegic refraction was done by retinoscopic measurement and spherical equivalent refraction (SER) of the eyes was calculated. The corneal curvature was determined with a Bausch and Lomb one position Keratometer (Bausch and Lomb Corp., USA). Results: The mean age, spherical equivalent, corneal curvature and corneal power were 20.44±2.24 years, ̶7.12±3.14DS, 7.72±0.26mm and 43.77±1.48D respectively. Most of the students had a myopia of -5.75 to -10.50DS (46.8%) and a corneal curvature of 7.61-7.90mm (46.82%). There was a difference between the corneal curvature of males and females (P=0.0001). A relationship was also found with gender and corneal curvature (P=0.001). Conclusions: This study found that high myopic females had shorter corneal curvature, with greater corneal powers than their males counterparts (P<0.01). We also found that gender had a significant relationship with the corneal curvature unlike age and the spherical equivalent which showed no relationship (P>0.01).